"The Christian in society": Reading Barth"s Tambach lecture (1919) in its German context - Kritzinger, J. N. J. (HTS teologiese studies, 2007)
This article analyses Karl Barth’s 1919 Tambach lecture on “The Christian in society” in the context of post World War I Europe. After describing Barth’s early life and his move away from liberal theology, the five sections of the Tambach lecture are analysed. Barth’s early dialectical theology focussed on: Neither secularising Christ nor clericalising society; Entering God’s movement in society; Saying Yes to the world as creation (regnum naturae); Saying No to evil in society (regnum gratiae); respecting God’s reign as beyond our attempts (regnum gloriae).